Stepping Together: The Young Generation Ready to Face Challenges Global Entrepreneurship at BumDes to Enhance Sociopreneurship Spirit - Bilqist, Nabila Putri; Putri, Milka Aletea Eka; Septiawan, Wahyu; Widiastuti, Anik (Universitas Mercu Buana, 2024)
Entrepreneurship in Indonesia, particularly among the younger generation, is a trending topic as young entrepreneurs compete to present innovative ideas for success in domestic and international markets. This article discusses the readiness of the younger generation to face global entrepreneurial challenges at BumDes. This research aims to assess how prepared the younger generation is to confront the challenges of global entrepreneurship at BumDes, to enhance the spirit of sociopreneurship. This research was carried out using qualitative methods with a descriptive approach. Data collection was carried out through a literature study, which is a technique for collecting and analyzing data originating from various relevant literature sources or documents. This research explores the concept of global entrepreneurship, the younger generation and global entrepreneurship, trends and case studies of the younger generation in global entrepreneurship, the sustainability of social entrepreneurship, obstacles to the readiness of the younger generation in facing global entrepreneurial challenges, and the efforts of the younger generation in facing global entrepreneurial challenges that require synergy, parties, and fields. The development of entrepreneurial spirit, enthusiasm, and behavior in the younger generation is one of the basic needs and important requirements for the Indonesian nation; therefore, this research can offer helpful conclusions for the government, educational institutions, and other stakeholders in supporting the entrepreneurial development of the younger generation. In the era of globalization